Controlled hydrothermal synthesis of BiOxCly/BiOmBrn/g-C3N4 composites exhibiting visible-light photocatalytic activity. (1st November 2021) - Chou, Yu-Chen; Lin, Yu-Yun; Lu, Chung-Shin; Liu, Fu-Yu; Lin, Jia-Hao; Chen, Fu-Hsuan; Chen, Chiing-Chang; Wu, Wu-Tsan
Abstract: The first systematic synthesis of bismuth oxychloride/bismuth oxybromide/graphitic carbon nitride (BiOx Cly /BiOm Brn /g-C3 N4 ) nano-composites used a controlled hydrothermal method. The structure, morphology and characteristic of BiOx Cly /BiOm Brn /g-C3 N4 photocatalyst were measured by XRD, UV–vis-DRS, FT-IR, FE-TEM, FE-SEM-EDS, PL, BET, HR-XPS and EPR. Under visible light irradiation, the photodegradation activity was evaluated for the decolorization of crystal violet (CV) and 2-hydroxybenzoic acid (2-HBA) in aqueous solution. The catalytic performance showed that, when using sample BB2C1-4-250-30 wt% g-C3 N4 composite as a photocatalyst, the best reaction-rate-constant ( k ) was 0.071 h −1 . It was 1.5 times higher than the k value of BB2C1-4-250 as a photocatalyst. From the scavenging effect of various scavengers, the results of EPR showed that reactive OH was the main scavenger, while O2 −, h + and 1 O2 were the second scavenger in CV degradation. In this study, a possible photodegradation mechanism was proposed and discussed. In this work, our method of BiOx Cly /BiOm Brn /g-C3 N4 preparation could be used for future mass production and the BiOx Cly /BiOm Brn /g-C3 N4 composite materials could be applied to the environmental pollution control in future. Graphical abstract: Figure abstract. Schematic diagram of synthesis method and photocatalysis for as-prepared BiOx Cly /BiOm Brn /g-C3 N4 under different conditions. Image 1 Highlights: This is the first report on a series of BiOCl/BiOBr/g-C3 N4 heterojunctions. BiOCl/BiOBr/g-C3 N4 can be prepared via the hydrothermal method. The efficiency is enhanced apparently for BiOCl/BiOBr/30 wt % g-C3 N4 . Photocatalytic mechanism of BiOCl/BiOBr/g-C3 N4 was investigated and discussed. OH plays the major role; O2 −, 1 O2 and h + plays the minor in the CV degradation.